A synthesis of freshwater forested wetland soil organic carbon storage - Sapkota, Yadav; Berkowitz, Jacob F.; Stagg, Camille L.; Busby, Ryan R. (Frontiers in Forests and Global Change, 2025)
Freshwater forested wetlands account for 76% (918 M ha) of the total global wetland extent. However, freshwater forested wetlands are difficult to distinguish from upland forest due to canopy coverage, the abundance of wetland-nonwetland mosaics, seasonal hydropatterns, and fewer readily observable connections to large surface water bodies relative to marshes and other emergent habitats. Therefore, freshwater forested wetland ecosystems are often misclassified as upland forests in carbon accounting models, underestimating soil organic carbon (SOC) storage. This study highlights freshwater forested wetland SOC accounting challenges and presents SOC densities/stocks from a global literature synthesis across different freshwater forested wetland types. We reviewed 374 forested wetland articles, compiling and calculating carbon densities by depth from 90 freshwater forested wetland studies to construct a database of 334 study sites including nine countries. The median (± median absolute deviation) SOC stock was 91.2 ± 46.4 Mg C ha−1 and 235.3 ± 125.6 Mg C ha−1 in the top 30 cm and 100 cm of soil, respectively. The tidal freshwater forested wetland had highest SOC stock (341.6 ± 98.4 Mg C ha−1) in the upper 100 cm soil profile followed by rainforest (285.6 ± 75.8 Mg C ha−1), non-tidal swamps (229.3 ± 120.4 Mg C ha−1), and floodplain forested wetlands (176.6 ± 84 Mg C ha−1). Within the conterminous United States forest type groups, the Tsuga/Picea group had the highest median SOC stocks (353.6 ± 82.9 Mg ha−1) in the top 100 cm of soil followed by Quercus/Pinus (246.6 ± 82.3 Mg ha−1) and Quercus/Liquidambar/Taxodium (207.9 ± 87.7 Mg ha−1) groups, likely driven by variability in litter degradability, wetland hydroperiod, geomorphic positions, and regional climatic factors. This literature synthesis highlights SOC accounting in freshwater forested wetland carbon pools when estimating carbon stocks and fluxes. Results can be used to improve carbon modeling outcomes, as well as inform regional, national, and global management of wetland carbon resources.